INTEGRATED TOURISM DEVELOPMENT OF GENGGELANG VILLAGE THROUGH SIGADis APPLICATION AND WEB VIRTUAL TOUR - Hamidy, Rasyid Ridho; Iskandar, Muhammad Joni; Parmi, Handri Jurya; Partama, I Gede Yudha; Ananda, Komang Dean; Pandawana, I Dewa Gede Agung (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
The development of digital-based tourism is increasingly needed to reach tourists who are looking for virtual experiences before visiting in person. This community service aims to develop the potential of natural tourism in Genggelang Village through the application of digital technology in the form of the Si Gadis application and virtual tour website. Si Gadis application is designed as an interactive platform that presents complete information about Genggelang tourism, including maps, routes, and destination descriptions. Meanwhile, the virtual tour website provides a visual tour experience that allows prospective tourists to explore the natural beauty and facilities available online. The methods used in this community service activity include field observations, interviews with local tourism managers, and the development of a digital-based system carried out by the team. The expected results of this community service are an increase in the number of tourist visits to Genggelang Village and an increase in local people's understanding of the importance of adapting technology in tourism development. In addition, Si Gadis application and virtual tour website are expected to be a model for tourism development in other villages with similar natural potential.